Thrombophilia and its impact on pregnancy - Pabinger, I. (Hämostaseologie, 2008)
In recent years thrombophilia has gained much attention as a risk factor for pregnancy complications. Whereas there is an established correlation between antiphospholipid-antibodies and pregnancy loss, data for other risk factors of thrombosis are less well established. Data suggest associations with antithrombin deficiency, hyperhomocysteinemia and also with factor V Leiden, prothrombin G20210A variation and protein S-deficiency. The association of thrombophilia with pre-eclampsia is still under discussion. A limited number of prospective studies did not reveal an increased risk for pregnancy complications in unselected women with thrombosis risk factors. In a single study low molecular weight heparin seemed to have a positive effect on pregnancy outcome after previous single or recurrent abortions. Experience in prevention of pre-eclampsia by administration of prophylactic heparin is very limited. Data on pregnancy complications in women with known heritable thrombophilia or a history of thrombosis are inconsistent as well. These women usually have a favourable pregnancy outcome. Conclusion: Thrombophilia screening might be justified in women with pregnancy loss. Treatment with low molecular weight heparin might be considered for those with pregnancy loss and thrombophilia. Further prospective studies and controlled interventional trials are urgently needed.
Keywords: Thrombophilia; pregnancy; fetal loss; abortion; pre-eclampsia; stillbirth